2020
DOI: 10.3390/w12030640
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Local Scour around Caissons under Unidirectional and Tidal Currents

Abstract: Local scour around caissons under currents has become one of the main factors affecting the safety of foundation construction and operation in coastal and offshore bridge engineering. Local scour occurs not only in the operation stage, when the caisson has settled into the sediment, but also in the construction stage, when the caisson is suspended in water. In this study, the local scour induced by unidirectional and tidal currents around settled caissons with different cross-sections (circular, square, and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Lo contrario sucede al variar la pila a una redondeada, donde sí se presentan cambios en la erosión de estos tipos de materiales. Esto se debe, en términos generales, al hecho de que sobre la cara de la pila cuadrada se concentra mayor energía; según los resultados de investigaciones recientes de Du y Liang [34] y Xiang et al [35], la resistencia del suelo al transporte depende más de su gradación (entrabamiento), que del contenido de partículas finas.…”
Section: Resultados Y Discusionesunclassified
“…Lo contrario sucede al variar la pila a una redondeada, donde sí se presentan cambios en la erosión de estos tipos de materiales. Esto se debe, en términos generales, al hecho de que sobre la cara de la pila cuadrada se concentra mayor energía; según los resultados de investigaciones recientes de Du y Liang [34] y Xiang et al [35], la resistencia del suelo al transporte depende más de su gradación (entrabamiento), que del contenido de partículas finas.…”
Section: Resultados Y Discusionesunclassified
“…The sediment transport in the area is likely onshore-offshore with little tidal flow and rocky reefs surrounding the region. Recent studies such as Lancaster et al [30] and Qiqi et al [31] demonstrated that significant scouring on a square caisson can occur at all four corners. Scour could hamper the integrity if sediments were removed from underneath the structure at specific points causing a seaward tilt and settlement, especially in such an energetic shallow water environment with poorly compacted sand and velocities near the bottom exceeding values of 1 m/s.…”
Section: Discussionmentioning
confidence: 99%
“…The stream hitting the bottom causes the horseshoe vortices formation (3 in Fig. 1) [4,5]. Initial vortices are formed, eventually taking the form of a lee-wake vortex (4 in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Three stages of the scouring process can be distinguished: the initial stage related to the scouring initiation, the proper stage, which is the period of scour development and deepening, and the final stage, in which the shape stabilization could be observed. The most significant initial stage could be pointed to, which is characterized by the high stream velocities occurrence in the bottom region and high stream turbulence [4][5][6][7][8]. The water surface elevation along the river reach depends not only on the hydraulic structure properties but also on the local granulometric conditions, which can be quantitatively characterized by hydraulic resistance coefficients.…”
Section: Introductionmentioning
confidence: 99%